PENGARUH PENGALAMAN KERJA, SKEPTISME PROFESIONAL DAN INDEPENDENSI AUDITOR TERHADAP PENDETEKSIAN KECURANGAN KLIEN PADA KANTOR AKUNTAN PUBLIK (KAP) DI KOTA PALEMBANG - Rusmida Jun Harahap; Shelly Faria Tobing (Universitas Tridinanti, 2020)
This study aims to analyze the effect of work experience, professional skepticism and independent auditors on client fraud detection. Primary data is the result of a questionnaire from the Palembang City Public Accountant Office. The statistical method uses multiple linear regression. The sample method uses convenience sampling. Hypothesis testing of the coefficient of determination, F test, and t test. The results of the multiple linear regression test can show that there is a significant positive effect of the work experience, professional skepticism and independence variables on the detection of client fraud, where Y = 1.575 + 0.036X1 + 0.586X2 + 0.542X3 + e. The result of the coefficient of determination stated that 89.5% of the detection of fraud by this study. The F test (simultaneous) shows that work experience, professional skepticism, and independence jointly influence fraud detection with Fcount> Ftable (79.686> 3.19) and the significant level is less than 0.05 (0.000 <0.05) . The results of the t test (partial) show that professional and independent skepticism has a significant effect on fraud detection with the statistical results for the variable professional skepticism, namely tcount 2.847, which means tcount> ttable (2.847> 2.048) and the level of sig. below 0.05, which is 0.008. As for the independence variable, the t-count value is 3.841, which means that tcount> ttable (3.841> 2.048) and the significant level is below 0.05 (0.001 <0.05). Work experience has no effect in the detection of fraud with the results of statistical data tcount of 0.300, which means that tcount <ttable (0.300 <2.048) and a significant level above 0.05 is 0.766> 0.05.Keywords: work experience, skepticism, independence, cheating